Major Trends and New Business Models in Supply Chain and Entrepreneurship After the Covid-19 Crisis - Negrutiu, Cristian (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
The paper investigates the major trends and business models of the new reality after the Covid-19 crisis. Due to the vastness of the theme, the research will be focused on the areas of supply chain and entrepreneurship. These sectors are probably the most affected today, but, also, the ones that will experience a major change in the future. Building on insights and data from top management consultants, the findings revealed some commons trends, like digitization, transparency, localization, the rising of e-commerce and the contact-less economy. In conclusion, the author proposes a model based on a virtuous cycle of elements that will shape the business models of the future as a contribution to the research in the selected sectors.